Reposicionamento de fármacos e planejamento de novos compostos ativos contra Schistosoma mansoni - Neves, Bruno Junior (2016)
Schistosomiasis is a serious endemic disease caused by trematodes of the genus Schistosoma. Currently the control of this disease is based solely on the administration of praziquantel. However, its extensive use has raised concerns about the emergence of resistant worms and the need of discovering new anti-schistosomal drugs. Given the above, the main goal of this study was to design new S. mansoni thioredoxin glutathione reductase (SmTGR) inhibitors showing antischistosomal activity through cheminformatics tools and to repurpose new drugs for schistosomiasis employing bioinformatics tools. At the stage of drug design, binary QSAR models were constructed and validated to predict inhibitory activity of SmTGR, a validated target in schistosomes. From the individual models, consensus and consensus rigor models and were generated (CCRs = 0.87 and 0.91, respectively) and used for the virtual screening of 150,000 compounds. At the end of this process, 29 compounds were prioritized and purchased for biological evaluation. As a result, two new hits representing new molecular scaffolds showed EC 50 ≤ 3.5 µM to schistosomula and ≤ 6.0 µM for adult female worms, low cytotoxicity against WSS-1 mammalian cells (IC50 > 16 µM) and low reactivity with cysteine proteases (IC50 > 100 µM). In the second part of this work, that is drug repositioning, 2,114 proteins of S. mansoni were used in a search for orthologs in therapeutic drug target databases (DrugBank, TTD and STITCH). As a result, 215 drugs were predicted to interact with 49 schistosome proteins, of which 47 had already anti-schistosomal activity reported in the literature. Then, principal component analysis (PCA) and k-means showed that 115 drugs were in the chemical space of known anti-schistosomal agents, increasing the overall confidence of predictions. Among them, paroxetine (PAR), an antidepressant drug predicted to inhibit serotonin transporter proteins of S. mansoni (SmSERTs) presented antischistosomal activity against schistosomula (EC50 = 2.5 µM) and adult worms (EC50 = 5.1 µM and 9.9 µM for males and females respectively) of S. mansoni. Lastly, molecular docking studies with SmSERT-A and its ortholog in humans (hSERT) explored the molecular basis for antischistosomal activity of PAR and provided information for the design of more potent and selective analogs.